2012
DOI: 10.1002/app.36770
|View full text |Cite
|
Sign up to set email alerts
|

Rheological and thermal properties of polylactide/organic montmorillonite nanocomposites

Abstract: Polylactide/organic montmorillonite (PLA/OMMT) nanocomposites were prepared by melt‐compounding technique. Dynamic and steady rheological properties, as well as dynamic mechanical and thermal stability of the nanocomposites were evaluated using various characterization tools. It was found that the rheological behaviors of nanocomposites were related with both temperatures and OMMT loadings. At low OMMT loadings, the steady‐shear viscosities and the complex viscosities showed a Newtonian plateau in low frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 35 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…TCP molecules can migrate to the surface of the PLA blends forming an insulating layer and improving the thermal stability of the blends . Moreover, similar results have been reported by Wang et al They found that the char formation from the addition of MMT acted as a heat barrier, which inhibited the volatiles of the decomposition products resulting in the increased thermal resistance of the blends …”
Section: Resultssupporting
confidence: 73%
“…TCP molecules can migrate to the surface of the PLA blends forming an insulating layer and improving the thermal stability of the blends . Moreover, similar results have been reported by Wang et al They found that the char formation from the addition of MMT acted as a heat barrier, which inhibited the volatiles of the decomposition products resulting in the increased thermal resistance of the blends …”
Section: Resultssupporting
confidence: 73%
“…Furthermore, to investigate the effect of OMMT on the tensile ductility of PLA matrix, the tensile performance of PLA/OMMT (100/x) with various OMMT loadings also are presented in Figure . It can be pointed out that the incorporation of OMMT could improve the elongation at break of PLA slightly (from 3.5% for neat PLA to 4.3% with 1 phr OMMT) without EPDM, which is in accordance with the literature . However, compared to the minor toughening effect of OMMT on PLA/OMMT samples, the incorporation of OMMT made a stronger enhancement in the ductility of these PLA/EPDM/OMMT samples due to the great compatibilizing effect of OMMT in the immiscible PLA/EPDM blends.…”
Section: Resultsmentioning
confidence: 99%
“…The resulting platelet alignment decreases the apparent viscosity so that it approaches that of the neat polymer melt [32,31]. This ability to re-orient the silicates layers or tactoids in response to externally applied flows also controls the viscoelastic properties of the composites [33].…”
Section: Composites Characterizationmentioning
confidence: 99%